Analysing clickstream data: do paid and organic search affect each other?. (2017) - Bremer, Vincent; Funk, Burkhardt
Investments in both paid and organic search are crucial for today's online retailer. In this paper, we analyse how consumers respond to organic and paid search advertising and gain insight into the interrelationship between these online marketing channels. We use a binary logit model and Markov-Chain-Monte-Carlo techniques and analyse the interaction effects between paid and organic search and the conversion probability based on clickstream data from a major electronic retailer. Our findings indicate that there is a positive relationship: when consumers interact with both paid and organic search, a strong positive effect occurs towards the conversion probability in the short-term compared to when users only interact with one channel. Our findings are valuable for organizations in regards to their online marketing strategies and budgeting.